The Effect of Liquidity, Profitability, Operating Cash Flow, and Ownership Structure on Financial Distress (Study on Property and Real Estate Companies Listed on the IDX) - Pamungkas, Noto; Qatrunnada, Hasna Salsabila (AIBPM Publisher, 2023)
Financial distress is recognized as the preliminary phase of bankruptcy, resulting from numerous financial and non-financial factors.This study aims to assess the effect of liquidity, profitability, operating cash flow as financial ratios, also managerial and institutional ownership as ownership structure on financial distress. This study use real estate and property companies listed on the Indonesia Stock Exchange (IDX) in the period 2018-2021 as the population. From a total of 80 companies, 28 were selected as the sample for this study using a purposive sampling method that applies several specific criteria. The data were processed using SPSS version 25 with a quantitative approach through multiple linear regression analysis techniques. Since the classical assumption test results of this research do not meet the requirements, the data are modified using log-modulus transformation. The results show that liquidity, profitability, and operating cash flow variables affect financial distress. Moreover, managerial ownership and institutional ownership do not affect financial distress. The results of this study suggest that management should be able to maintain financial performance efficiently to avoid financial distress.